If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1a + 4a = -9 Combine like terms: -1a + 4a = 3a 6 + 3a = -9 Solving 6 + 3a = -9 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3a = -9 + -6 Combine like terms: 6 + -6 = 0 0 + 3a = -9 + -6 3a = -9 + -6 Combine like terms: -9 + -6 = -15 3a = -15 Divide each side by '3'. a = -5 Simplifying a = -5
| 2p-2=16 | | 2.2h=22-6 | | 3p-2=4-3p+6 | | 16x^4+79x^2=2 | | 40+15(x)=205 | | 40+15(9)= | | 40+15(4)= | | n^2+9n*10n+90=30 | | n-8-6=-12 | | 88-26=10(h-6) | | p-26=10(20-6) | | -38-4(15)= | | 7x-34=5y | | p-26=10(18-6) | | -38-4(12)= | | -38-4(6)= | | -a+4a= | | 18+9(x)=288 | | 18+9(24)= | | x^4-9*x^3+27*x^2-91*x=0 | | 45+18= | | -3x-5=-35 | | 4a-a=23 | | x-3y+2z=-28 | | 2(x+3)=14-x | | 5(x-3)=2(4x+1) | | 3(12-x)-6=2 | | -v+3=4 | | 3x+3y+z=-11 | | 32+4(x)=180 | | 224=-8m | | 39+3(x)=174 |